The Characterization and Evaluation of Dimensional Stability for Highly Stable Composites - Baolong Sun; Hansi Zhang; Xiaoyu Wang; Chuang Xue; Yue Qiu (IEEE Access)
In this study, we explored the dimensional stability of high-performance carbon fiber reinforced plastics (CFRP) under regulated thermal conditions. This study systematically examined the interplay between temperature variations and structural response via experimental characterization and analytical calculations, establishing a methodology for assessing material properties in dynamic thermal environments. By associating the temperature stability threshold with nanoscale dimensional fluctuations within the low-frequency domain, this study enhances our understanding of CFRP reliability in high-stability applications such as aerospace systems or optical instruments. The findings of this research suggest that the dimensional stability of the test specimens satisfies the fundamental standards for practical applications, and that achieving dimensional stability exceeding 1 nm/Hz ${}^{1/2}$ (0.005Hz~0.1Hz) through optimized thermal management is attainable. This offers actionable insights for material selection and design in domains requiring extremely high dimensional precision, bridging the essential gap between the fundamentals of materials science and practical engineering requirements.